RELIGIOUS EDUCATION IN SECULAR SOCIETY: REFLECTIONS ON THE RATIONALE AND (FUTURE) FORM OF RELIGIOUS TEACHING IN GERMANY - Könemann, Judith (Asian Horizons, 2018)
This essay addresses the current state and the future of religious education in Germany. In accordance with the German constitution (Grundgesetz), religious education is part of the regular curriculum of the public education system of the Federal Republic of Germany. It is faith-oriented and denominational. The question of the future of religious education as a faith-oriented and denominational school subject arises in light of massive changes in the religious landscape in Western Europe and, especially, in the face of an increasing plurality of religions and worldviews. This essay argues that, in light of religion regaining importance in the public sphere in Western Europe, being educated about religion becomes a necessary tool for acting in society. In the German education system, currently, there is no provision for religious education for non-religious people because of the denominational orientation of religious education. To reflect on this subject, first, this essay will give reasons for and a legitimation of religious education in the German public education system. After that, it will present ideas for an appropriate form of religious education in the public education system. These ideas refer to the organisational form, contents and didactical approaches.